1973
DOI: 10.1111/j.1432-1033.1973.tb03135.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of the Creatine‐Kinase Active Site Studied by Chromophoric‐Reagent Labelling

Abstract: The environment of the active site of creatine kinase has been investigated by means of three chromophoric reagents : 2-hydroxy-5-nitrobenzyl bromide, 2-methoxy-5-nitrobenzyl bromide and 2-(dansy1amino)ethyl monophosphate.1. The first two reagents are incorporated at the essential thiol groups. The effect of pH on the spectra of the 2-hydroxy-5-nitrobenzyl-labelled creatine kinase suggests that this reagent lies inside the active site near an ionized residue, while the 2-methoxy-5-nitrobenzyl group is apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
2007
2007

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Chemical modification studies have indicated that a thiol residue/subunit of creatine kinase can be modified by a variety of other thiol-specific reagents with concomitant loss of activity (Watts et al, 1961;Mahowald et al, 1962;Okabe et al, 1970;Roy et al, 1970;Brown and Cunningham, 1970; Milner-White and Watts, 1971;Roustan et al, 1973). What appears to be an "essential thiol" has been shown in all isoenzymes of creatine kinase and enzymes isolated from various mammalian sources (Watts, 1973), including the one currently under study (Roy et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical modification studies have indicated that a thiol residue/subunit of creatine kinase can be modified by a variety of other thiol-specific reagents with concomitant loss of activity (Watts et al, 1961;Mahowald et al, 1962;Okabe et al, 1970;Roy et al, 1970;Brown and Cunningham, 1970; Milner-White and Watts, 1971;Roustan et al, 1973). What appears to be an "essential thiol" has been shown in all isoenzymes of creatine kinase and enzymes isolated from various mammalian sources (Watts, 1973), including the one currently under study (Roy et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…NADP (sodium salt) was provided by Sigma. 2-(Dansy1amino)ethyl monophosphate was synthetized as previously described [19]. Sugars were obtained from Boehringer Mannheim GmbH (Mannheim, Germany), Prolabo or Calbiochem.…”
Section: Methodsmentioning
confidence: 99%
“…From this and the classical studies of Herskowitz [8] we conclude that the formation of the final complex of Scheme 1 results in the removal of one or more tryptophan residues from the interior of the creatine kinase molecule into an exposed polar environment. It is noteworthy that none of the tryptophan residues of the nude enzyme reacts with Koshland's tryptophan reagent [20]. When ethylene glycol is added to the system the amplitude of the difference spectrum decreases but there is a sharp increase as the temperature is decreased.…”
Section: Structural Comments On the Nitrate Complexmentioning
confidence: 99%